Internal Wave Observations Off Saba Bank - van Haren, Hans; Duineveld, Gerard; Mienis, Furu (Frontiers in Marine Science, 2019)
The deep sloping sides of Saba Bank, the largest submarine atoll in the Atlantic Ocean, show quite different internal wave characteristics. With the aid of two 350 m long arrays of high-resolution temperature T-sensor string and acoustic Doppler current profiler that were moored around 500 m depth for three weeks we observed that the surrounding waters were generally stratified in density layers of multiple sizes, that turbulence is about a factor of two less than the strong turbulence previously observed above comparable steep slopes above Atlantic seamounts and that near-bottom nonlinear turbulent bores are absent. Both the Banks’ north-side and south-side slopes are locally steeper than internal tide slope angles. However, the three times weaker north-side slope shows quasi-mode-2 semidiurnal internal tides over the range of observations, centered with dominant near-inertial shear around 150 m above the bottom, but generating the largest turbulence when touching the bottom and showing off-bank flowing turbid waters. In contrast, the steeper south-side slope shows quasi-mode-1 internal tides having occasionally excursions >100 m crest-trough, with weak inertial shear and smallest buoyancy scale turbulence periodicity occurring near the bottom and about half-way the water column, below abundant coral reefs in shallow <20 m deep waters. A -5/3 inertial subrange is found within the internal wave band at frequencies below the buoyancy frequency.